2010
DOI: 10.1002/emmm.201000099
|View full text |Cite
|
Sign up to set email alerts
|

V600E Braf induces gastrointestinal crypt senescence and promotes tumour progression through enhanced CpG methylation of p16 INK4a

Abstract: The majority of human colorectal cancers (CRCs) are initiated by mutations arising in the adenomatous polyposis coli (APC) tumour suppressor gene. However, a new class of non-APC mutated CRCs has been defined that have a serrated histopathology and carry the V600EBRAF oncogene. Here we have investigated the pathogenesis of serrated CRCs by expressing V600EBraf in the proliferative cells of the mouse gastrointestinal tract. We show that the oncogene drives an initial burst of Mek-dependent proliferation, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 48 publications
(73 reference statements)
4
116
0
1
Order By: Relevance
“…This was overcome by methylation of the CDKN2A promoter leading to the development of invasive carcinomas. 28 The mouse model confirms our findings in human serrated polyps.…”
Section: Discussionsupporting
confidence: 83%
“…This was overcome by methylation of the CDKN2A promoter leading to the development of invasive carcinomas. 28 The mouse model confirms our findings in human serrated polyps.…”
Section: Discussionsupporting
confidence: 83%
“…25,26 We found that induction of BRAF V600K induced significant DNA damage in the intestine, as demonstrated by immunofluorescence analysis of phosphorylated histone γH2A. However, we did not find increased apoptosis in BRAF V600K -induced intestinal tissues, as assessed by cleaved caspase 3 IHC (Supplementary Figure 8).…”
Section: Above)mentioning
confidence: 65%
“…This is in contrast to previous mouse models of oncogenic activation of BRAF, which used knock-in alleles. 18,26 As a consequence, BRAF V600K induction in our mouse model results in immediate and strong activation the MAPK cascade. Consequently, MAPK target genes in transgenic BRAF V600K mice were induced to levels characteristic of more advanced stages of tumor progression obtained in BRAF V637E knock-in mice.…”
Section: Discussionmentioning
confidence: 81%
“…However, recent evidence suggests that not all kinds of cells have the ability to enter in senescence when faced with the same stimuli. In fact, recent studies have shown that expression of oncogenic K-RAS in mice induces senescence in colonic cells, while small bowel cells become only hyperplasic (Bennecke et al, 2010;Carragher et al, 2010). These results suggest that something more than oncogenic stimuli is needed to induce senescence, and this secondary event seems to be tissue/cellular background specific.…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 97%
“…In the colon, two different patterns of p16 Ink4a overexpression have been observed. The first pattern is related to senescence in serrated adenomas, which have malignant transformation associated with p16 Ink4a downregulation (Carragher et al, 2010). The second pattern is characterized by a very low p16 Ink4a immunostaining in normal mucosa, with a progressively higher expression in aberrant crypt foci, non-serrated adenomas, primary carcinomas and metastatic tumors (Dai et al, 2000;Zhao et al, 2006).…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 99%